The snaking stability of passenger cars with light cargo trailers - Šušteršič, Gašper (Strojniški vestnik, 2014)
This paper presents research conducted to determine whether the detailed multibody system (MBS) model presented in the paper is applicable to modelling the snaking phenomenon and to validate the model, including the parameter values, so that it can be used in further research of vehicle safety systems. Experiments and simulations both show - and with good agreement - that the system of a passenger car and a cargo trailer can become unstable at motorway velocities if the trailer is loaded inappropriately. Based on an analysis of the measured data, the impact-damping phenomenon and its influence on snaking damping have been identified. An MBS analysis of the computational- fluid-dynamics-determined aerodynamic influences on the system's response to an impulse disturbance has shown these influences to be negligible. We have devised the principles and apparatus for measuring the steering-wheel angle, the articulation angle and the lateral force of the trailer's tow bar. Measuring the last of these makes possible an on-the-fly determination of the trailer's yaw inertia, one of the most influential parameters with respect to the snaking phenomenon.
Keywords: dinamika vozil; lahki tovorni priklopniki; računalniška simulacija dinamike tekočin; simulacija; sistem togih teles; skupina vozil; trčno dušenje; vijuganje